Sari-saring kasarian conceptual photographs of the self-representation of select LGBTQ young adults' gender identities and expressions in Davao City - Pongan, Pocholo Miguel a. (2019)
Sari-saring Kasarian explores how conceptual photography interpreted the self-representation of the gender identities and expressions on nine select LGBTQ young adults from Davao City. The stories told through the photographs root itself in authentic experiences shared by LGBTQ young adults from Davao City. Using J. Neil Garcia?s queer theory of ?panloob? and ?panlabas? as the foundation of this study along with the gaze of the photographer. The photographs serve as a channel that relayed the narratives and self-identity of the individuals shown in the photographs. The use of conceptual photography in this study is to visually present realities from author?s angle of vision, and further enhance the ability of the photos to depict self-expression. Even though conceptual photographs oppose how photographs depict truth, as they appear manipulated, staged and even amplified and that the researcher?s gaze is the one that constructs their identities in the photographs, the photographs in this study are still strongly anchored on reality. Being in a predominantly catholic country that has long shunned the reality of these existing realities this study chose to make them visible through photography and at the same times serves to remind that the only individuals who can define the LGBTQIA+ are themselves.